2003
DOI: 10.1029/2002jd002250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aerosol size distributions, radiative properties, and optical depths determined by aircraft observations and Sun photometers during SAFARI 2000

Abstract: [1] The Meteorological Office C-130 aircraft performed a dedicated flight over the Etosha Pan surface-based Aerosol Robotic Network (AERONET) Sun photometer site on 13 September 2000 during the Southern African Aerosol Regional Science Initiative (SAFARI 2000) intensive measurement campaign. Aerosol optical depths at different wavelengths, t aerl , are derived from in situ measurements of the scattering and absorption coefficients and from various radiometric measurements and compared to those derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
173
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(203 citation statements)
references
References 25 publications
27
173
1
2
Order By: Relevance
“…Allowing for a range of +/−0.03 in the single-scatter albedo yields a range of +/−0.5 K d −1 in the heating rate at the altitude of peak heating. This range in single-scatter albedo is consistent with estimates of measurement uncertainties in singlescatter albedo and is greater than the range of average values reported for different flights during the SAFARI 2000 campaign (Haywood et al, 2003).…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Allowing for a range of +/−0.03 in the single-scatter albedo yields a range of +/−0.5 K d −1 in the heating rate at the altitude of peak heating. This range in single-scatter albedo is consistent with estimates of measurement uncertainties in singlescatter albedo and is greater than the range of average values reported for different flights during the SAFARI 2000 campaign (Haywood et al, 2003).…”
Section: Methodssupporting
confidence: 66%
“…The aerosols are distributed in a half-sinusoidal profile from 1.5 to 4.2 km altitude with peak aerosol concentration at about 3 km altitude. Aerosol optical properties are derived from in-situ observations during the SAFARI 2000 field campaign (Haywood et al, 2003) where it is reported that the single-scatter albedo was 0.89 at 0.55 µm. A spectral dependence of the single-scatter albedo of −0.1 µm −1 is used to extrapolate the 0.55 µm value to other wavelengths for the broadband radiative transfer calculations based on the column-integrated surface sun photometer measurements also made during SAFARI 2000 (Eck et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The adopted value of n r is 1.53, taken from the DODO experiment , which was focused on Saharan dust and conducted in the same general time frame as NAMMA. The same value was also reported in an earlier work (SHADE) by Haywood et al (2003). The value of n i was set to 0.0022, derived from this study (see discussion in Sect.…”
Section: Dust Particle Scattering Closure Assessmentmentioning
confidence: 99%
“…These included: number size distributions from a Passive Cavity Aerosol Spectrometer Probe (PCASP Model 100, 0.1-3 µm radius, PMS Inc.), scattering coefficient at 450, 550 and 700 nm from an integrating nephelometer (model 3563, TSI Inc.), absorption coefficient at 567 nm from a Particle Soot Absorption Photometer (PSAP, Radiance Research), total sub-micron number concentration from a Condensation Particle Counter (CPC, model 3010, TSI Inc.), and aerosol composition from online aerosol mass spectrometry, offline filter analysis, and Volatile Aerosol Concentration and Composition (VACC; Brooks et al, 2007) thermograms. A mixture of profiles, straight and level runs and orbits were conducted over both the Po Valley and Northern Adriatic Sea, in a manner similar to that flown by the Met Office C-130 aircraft during various missions -the Southern African Regional Science Initiative (SAFARI 2000;Haywood et al, 2003), the Saharan Dust Experiment, the Tropospheric Radiative Forcing Observational Experiment, and the second Aerosol Characterization Experiment (SHADE, TARFOX, ACE-2; Osborne and Haywood, 2005). A flight over the Black Sea was also conducted and is described in detail in Cook et al (2007).…”
Section: Methodsmentioning
confidence: 99%